Praten met kinderen en jongeren over seksualiteit en relaties : gids voor ouders. - Klaï, Telidja; Hendrickx, Kenny; Lambrechts, Chris (Antwerpen : Sensoa Gezinsbond, 2006)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure